The voluntary intake and digestibility of combinations of cereal crop residues and legume hay for sheep - Butterworth, M.H.; Mosi, A.K. (1986)
Examines the effects of supplementing diets based on common Ethiopian crop residues (teff, wheat and oat straws and maize stover) with different proportions of hay made from a common local clover, Triofolium tembense.